Oksidentalism as an Islamic Response to the Advancement of Western Civilization; Study of Hassan Hanafi's Thought - Siswoyo Aris Munandar (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2021)
Abstract: It is a fact that the West is now economically more advanced than the East. This matter is considered unanimously by most Easterners to be entirely oriented to him. The West exports an ideology that all countries in the world seem unable to reject, then developing countries agree with it, then struggle with the number one puritan discipline and cunning attitude to be able to advance economically and technologically. It seems that it is a necessity for a comprehensive human development. Various criticisms have been raised, but nothing has been able to stop the power of this understanding. In fact, it made him modify an even more accurate strategy. The question that arises then is, why did the homeland liberation movement succeed in escaping from military occupation but failed to defend economic, political, cultural and civilizational independence? Why are the majority of independent countries, after gaining their independence increasingly following the West in the fields of food, weaponry and modernization of society? This paper is a study with the type of research library that intends to discuss Hassan Hanafi's ideas regarding accidentalism which is a form of Islamic response to the progress of Western civilization. The conclusion obtained from this study is that incidentalism is an act of resistance from the East to study the West in more depth. According to Hassan Hanafi, in seizing the glory of the East, it requires the attitude of three renewal tradition projects, namely, first, our attitude towards old traditions, our attitude towards Western traditions, and our attitude towards reality. Even with a harsh and critical tone, Hanafi's occidentalism does not intend to do a complete reversal in the sense of replacing the position that had been played by orientalism. If earlier orientlism was not in a neutral position and was mainly dominated by European consciousness structures formed by modern civilization, Hanafi designed orientalism as a neutral scientific discourse. Keywords: Orientalism, Occidentalism, West, East, Hassan Hanafi